Laparoscopy-assisted Robotic Myomectomy Using the DA Vinci System - Shih-Peng Mao; Hung-Cheng Lai; Fung-Wei Chang; Mu-Hsien Yu; Cheng-Chang Chang (Elsevier, 2007)
Objective: To report a case of a woman with a large uterine myoma who underwent laparoscopy-assisted robotic myomectomy using the da Vinci system. Case Report: A 38-year-old, gravida 2, para 2, female patient presented to our office with a chief complaint of lower abdominal pressure and pain. A pelvic sonogram disclosed a subserosal myoma with a broad base, measuring approximately 9 × 8 × 7 cm, which was located at the anterior uterine wall. The patient insisted on preserving her uterus and was concerned with the cosmetic results after the surgery. She showed willingness to undergo myomectomy using the newly developed laparoscopy-assisted robotic system (da Vinci) and signed the consent form. The operation time was about 3 hours, with an estimated blood loss of 150 mL. The patient passed flatus and resumed oral intake on the following day. Conclusion: Minimally invasive surgery is the trend of the future. Robot-assisted laparoscopic surgery is a new technique for myomectomy. This robotic system provides a three-dimensional operative field and an easy-to-use control panel, which may be of great help when applying the suturing techniques and may shorten the learning curve. More experience with and long-term follow-up of robotic surgery may be warranted to further validate the role the robot-assisted approach in gynecologic surgery.